Evaluation of the Capparis Herbacea Willd's Chemistry, Antioxidant and Cytotoxic Activity - Tleuberlina, Orynbassar; Mamurova, Asem; Iskakova, Zhanar; Aibuldinov, Yelaman; Kolpek, Ainagul; Kopishev, Yeldar; Satbaeva, Gulbarshyn; Mukazhanova, Zhazira; Kurmanbayeva, Meruyert (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2023)
Background: The Capparidaceae family includes the medicinal herb Capparis herbacea Willd. The aerial and underground parts of plant C.herbacea were studied for their chemical composition, antioxidant, and cytotoxic properties.Methods: Using gas chromatography with mass spectrometric detection (7890A/5975C), 94 chemicals were identified in ethanol extract from leaves, roots, seeds, and stems of C. herbacea. Main components were (leaves) phytol 18.16%, hexanedioic acid, bis(2-ethylhexyl) ester 16.75%, vitamin E 11.95%, (roots) sucrose 13.94%, hexadecanoic acid, ethylester 22.80%, octadecanoic acid, ethylester 37.77%; (seeds) hexadecanoic acid, ethylester 13.96%, ethyl9.cis.,11.trans.-octadecadienoate 48.54%, bis(2-ethylhexyl) phthalate 9.77%; (stems) 1-propene-1,2,3-tricarboxylic acid, tributyl ester 42.69%, and tributylacetylcitrate 19.63%. Nine components were identified in the makeup of the C. herbacea sample's essential oil using the method of chromatography-mass spectrometry.Results: The main components were (in%): T-cadinol (29.56), meta-cymene (16.12), pulegone (14.11), and σ-amorphene (12.26). Chloroform and methanol extracts of Capparis herbacia roots at concentrations of 1 mg/ml showed higher average antioxidant activity, while ethyl acetate root extract at concentrations of 0.75 and 1 mg/ml showed higher average antioxidant activity compared to gallic acid AOA.Conclusion: In addition, plant extracts have cytotoxic activity. Essential oils of leaves and stems, fruit and roots of Capparis herbacia plants exhibited cytotoxicity, all larvae died, and larval mortality was 96%.
Keywords: cytotoxic